Combined heat and mass transfer performance enhancement by nanoemulsion absorbents during the CO2 absorption and regeneration processes. (October 2019) - Lee, Wonhyeok; Kim, Seonggon; Xu, Ronghuan; Kang, Yong Tae
Highlights: Nanoemulsion CO2 absorbents are manufactured using methanol and undecane. The highest thermal conductivity is obtained at the undecane concentration of 0.05 vol%. The average absorption rate increases by 13.04% at 0.05 vol% of undecane compared to the base absorbent. The average regeneration rate increases by 22.03% at 0.05 vol% of undecane compared to the base absorbent. Various mechanisms for heat and mass transfer enhancements by nanoemulsion absorbents are discussed. Abstract: Nanoemulsion absorbents are manufactured using methanol and undecane for CO2 absorption and regeneration performance enhancement. The most representative physical CO2 absorbent, methanol, is mixed with undecane and dispersed by the ultrasonication method. Span 60 and Tween 60 are used to obtain a high dispersion stability. To determine the effect of undecane concentration on the combined heat and mass transfer performance during the absorption and regeneration processes, various concentrations of nanoemulsion absorbents are prepared. The thermal conductivity of the nanoemulsion is also measured to estimate the effect of nanodroplets on the heat transfer performance. It is concluded that the average absorption rate increases by 13.04% at 0.05 vol% of undecane and the average regeneration rate does by 22.03% at 0.05 vol% compared to the base absorbent. Various mechanisms for combined heat and mass transfer performance enhancement by nanoemulsion absorbents are discussed. It is concluded that the mechanism of regeneration performance enhancement by the thermal effect in the nanoemulsion absorbents is less effective compared to that in the nanofluid absorbents.